Investigating teachers’ happiness in the contexts of spiritual well-being and stress in Turkey - Ekşi, Halil (Mental health, religion & culture, 2020)
This study aims to examine whether stress and the dimensions of spirituality (i.e., anomie, transcendence, and harmony) affect teachers' well-being. A total of 378 teachers working in various cities in Turkey have participated in the research. The PERMA, Spiritual Well-Being, and Perceived Stress Scales were used to collect the data. The structural equation model and correlational was used to analyse the data. According to the results, stress is a meaningful predictor of anomie; anomie is a meaningful predictor of transcendence, harmony with nature, and happiness; and transcendence is a meaningful predictor of happiness. Stress and harmony with nature are not meaningful at predicting happiness. The obtained data were considered to provide psychological counselors with information on how to use spirituality in the counseling environment and information on the relationships between stress and well-being.